Video game modding in the U.S. intellectual property law: Controversial issues and gaps - Ch. A. Lee (Цифровое право, 2022)
This essay’s purpose is to illustrate a broad understanding of legal issues and gaps in U.S. law regarding video game modifications. Digital entertainment technology develops so quickly that often new technology does not fit precisely into current law and statutes. Two different approaches to video game modification are explored pertinent to companies’ different attitudes toward modification by third parties and end-users. These two approaches include companies that encourage third party modifications, and companies that want to deter against third party modifications. Then, issues and risks of modification are explored through potential breach of contract, copyright infringement, and reverse engineering. The author analyzes the relevant court rulings on the matter of distributing these risks. Besides there are different forms of affirmative defenses such as fair use in the U.S case law which are also discussed in the article. Finally, gaps in the law and ownership issues regarding modifications are shown in the cases involving Blizzard Entertainment Inc. This essay is meant to illuminate the dichotomy of laws and courts protecting the interests of copyright holders, giving them protection and incentive to continue creating, versus anti-monopolistic rules, and providing the ultimate beneficiaries of video games the right to modify them.